EXPERIMENTAL VERIFICATION OF THE EFFECTIVENESS OF IMPLEMENTATION OF PEDAGOGICAL CONDITIONS OF FORMATION OF PROFESSIONAL QUALITIES OF THE FUTURE BANKING SPECIALISTS - Benkovska Н.Б. (Journal of Information Technologies in Education (ITE), 2015)
Today there is an urgent need for reform in education. In particular those educational fields are need to reform that train specialists to build an effective economic system of the country,including the banking system. Thus, there is a need to study the effectiveness of implementation of pedagogical conditions of formation of professional qualities of future specialists of Banking and identify the priority areas of development of relevant education field. Considering on the specificity of training banking specialists, the focus of research is to determine the role of ICT both in future work and in preparing students for future professional activity. Thus, on the efficiency of formation of professional qualities of future banking specialists in the course of their professional training will have a positive impact such educational facilities as updating interdisciplinary integration of professional disciplines, activation of interactive learning tools for students and simulation of special learning situations aimed to awareness of the importance of competencies to carry out the professional activities. The implementation of pedagogical conditions of formation of professional qualities of future banking specialists will provide the stable positive dynamics of formation of professional qualities of future banking.